PENGARUH LABEL HALAL DAN HARGA TERHADAP KEPUTUSAN MEMBELI PRODUK KOSMETIK WARDAH (Studi Pada Mahasiswi Prodi Manajemen Universitas Bengkulu) - Fenti Mayang Sari; Andy Makhrian; Khairil Buldani (Professional: Jurnal Komunikasi dan Administrasi Publik, 2018)
This study aims to find out how the influence between halal and price labels influences consumers in making buying decisions, to know more about identifying products, buying and using products. This study uses a closed questionnaire in data collection and literature studies and other references related to research problems. The sample in this study was a student of UNIB management which was taken using a purposive sampling method with the criteria of using wardah cosmetic products for approximately 4 months from this study and having knowledge of beauty care, then analyzing the data using statistical tests of multiple linear regression analysis (F test and T test). Based on the results of the research, it can be seen halal and price labels. So it can be concluded that the results of halal and price labels partially (T Test) null hypothesis (H0) are accepted which means there is no positive influence, but overall both of these variables influence consumers' decision to buy and choose wardah products.